The Role of Paris Agreement in the Application of the Common but Differentiated Responsibilities and Respective Capabilities (CBDR-RC) Principle - Puti Ayla Zafira Adriansyah; R. A. Gusman Catur Siswandi; Imam Mulyana (Padjadjaran Journal of International Law, 2023)
The Paris Agreement is one of the climate change agreements that formed on the basis of voluntarycontributions and uses the principle of Common but Differentiated Responsibilities and RespectiveCapabilities (CBDR-RC) as the ground norm of its implementation. The principle allows state parties todetermine their own targets and efforts to reduce emissions on a national and global level. However, theprinciple poses a challenge to the Agreement because it could lead to non-compliance by the stateparties and reduce their ambition to achieve net-zero emission targets. In addition, the question arises asto how international law can encourage compliance with the CBDR-RC principle and what efforts aremade to achieve an effective implementation. This article provides an understanding of the role ofinternational law in accommodating the dynamics of the CBDR-RC principle in the context of climatechange. It also discusses the role of international law in the compliance process and its relation tocompliance mechanisms as an effort to encourage the implementation of CBDR-RC principle. The resultindicates that international law through the principle can encourage state parties to comply by filling thegap in the Agreement which is the soft rules. Therefore, a good compliance committee and rules thatconsist of an easy way for state parties to comply are needed to achieve an effective implementation ofthe principles.